Solar photocatalytic activities of porous Nb-doped TiO2 microspheres by coupling with tungsten oxide. (March 2015) - Kou, Yanqiang; Yang, Jikai; Li, Bing; Fu, Shencheng
Graphical abstract: Highlights: Nb-TiO2 /WO3 was prepared by USP method combined impregnation method. Nb-doping extend the spectral absorption of TiO2 into visible spectrum. Nb-TiO2 /WO3 has a similar optical band gap as Nb-TiO2 . PL spectra indicate WO3 can accept the photoexcited electrons from Nb-TiO2 . Nb-TiO2 /WO3 shows higher activity than TiO2 and Nb-TiO2 under solar light. Abstract: Nb doped TiO2 microspheres modified with WO3 (Nb-TiO2 /WO3 ) was prepared by ultrasonic spray pyrolysis method combined with impregnation method. The microspheres were characterized with SEM, TEM, XRD, BET, photoluminescence and UV–vis absorption spectra. The Nb-doping was observed to extend the spectral absorption of TiO2 into visible spectrum, and the absorption onset was red-shifted for about 88 nm compared to pristine TiO2 microspheres. Nb-TiO2 /WO3 microspheres do not display a red-shifted absorption edge compared with Nb doped TiO2 microspheres. Under solar irradiation, Nb-TiO2 /WO3 microspheres showed higher photocatalytic activity for methylene blue degradation compared with that of pure TiO2 microspheres and Nb doped TiO2 microspheres, which could be ascribed to the extended light absorption range and the suppression of electron-hole pair recombination.